2014
DOI: 10.1002/stem.1769
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Fate of Limbal Epithelial Progenitor Cells in the Murine Cornea

Abstract: Stem cell (SC) division, deployment, and differentiation are processes that contribute to corneal epithelial renewal. Until now studying the destiny of these cells in a living mammal has not been possible. However, the advent of inducible multicolor genetic tagging and powerful imaging technologies has rendered this achievable in the translucent and readily accessible murine cornea. K14CreERT2‐Confetti mice that harbor two copies of the Brainbow 2.1 cassette, yielding up to 10 colors from the stochastic recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
158
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(173 citation statements)
references
References 61 publications
11
158
2
2
Order By: Relevance
“…For mouse corneas, the rate of centripetal movement has been estimated as 11-26 µm/d using three different approaches involving direct observations of labelled cells. Corneal epithelial cells labelled with India ink moved 17 µm/d over 7 d [62] , patches of brightly fluorescent cells moved 26 µm/d over 7 wk in mosaic GFP transgenic mice [63] and fluorescent clones of cells extended 11 µm/d over 12 wk in K14-CreERT2;R26R-confetti transgenic mice (from 9 to 21 wk after tamoxifen-activation of the reporter transgene) [64] . Furthermore, the evidence from the mosaic GFP transgenic mice [63] and tamoxifen-activated reporter transgenic mice [64] demonstrated that the same clonal lineage of cells moved across the full radius from the periphery to the centre.…”
Section: Movement Of Corneal Epithelial Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…For mouse corneas, the rate of centripetal movement has been estimated as 11-26 µm/d using three different approaches involving direct observations of labelled cells. Corneal epithelial cells labelled with India ink moved 17 µm/d over 7 d [62] , patches of brightly fluorescent cells moved 26 µm/d over 7 wk in mosaic GFP transgenic mice [63] and fluorescent clones of cells extended 11 µm/d over 12 wk in K14-CreERT2;R26R-confetti transgenic mice (from 9 to 21 wk after tamoxifen-activation of the reporter transgene) [64] . Furthermore, the evidence from the mosaic GFP transgenic mice [63] and tamoxifen-activated reporter transgenic mice [64] demonstrated that the same clonal lineage of cells moved across the full radius from the periphery to the centre.…”
Section: Movement Of Corneal Epithelial Cellsmentioning
confidence: 99%
“…When Majo et al [1] proposed the CESC cell hypothesis they also proposed that the corneal and conjunctival epithelia continuously expand towards the limbus, which they described as a zone of equilibrium, so any movement in the corneal epithelium was predicted to be centrifugal. This is inconsistent both with the absence of movement in the conjunctiva [62,65] and the convincing, direct evidence that movement of corneal epithelial cells is centripetal not centrifugal [62][63][64] . The evidence for centripetal cell movement in the corneal epithelium is inconsistent with the CESC hypothesis as originally proposed [1] but there is no need to link the stem cell location and movement aspects of the original CESC hypothesis.…”
Section: Movement Of Corneal Epithelial Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Altogether, the Br2.1 cassette allows the random, inducible, and tissue specific expression of one out of four distinct fluorescent genes in each targeted cell. In fact, when a larger number of color combinations is needed, one can generate homozygous mice that contain 2 alleles of Br2.1, thus resulting in the expression of 2 color tags for each cell and in raising the number of possible color combinations to 10 22 . Some of the Br mouse strains enable the expression of a much greater number of possible color combinations since multiple copies of the cassette were integrated into their genome 16 .…”
Section: Introductionmentioning
confidence: 99%